Al-Jazari on automata - Ushama, Imama Karim Manba; Shafie, Amir Akramin (IIUM Press, 2011)
This chapter investigates different spheres of work that AI-lazari contributed in the field of automata. The objective of the chapter is to discover whether his contributions are truly novel and to seek whether his contributions cater around automata. Furthermore, this chapter looks into the information that has been provided by his book and whether this information provided is accurate enough to be defined under the domain of selfautomation. The methodology used in developing this chapter relies on reliable sources. The significance of this chapter is to identify the contribution that AI-lazira had made in automating his systems.Automata is a term which describes a self-operating machine. This refers to robots usually and specifically a self-operating robots also known as automated robots. Automata theory generally refers to automation of abstract machines. Abu aI-'Iz Ibn Isma'n ibn al-Razaz al-lazarT lived in the Islamic Golden Age. He is best known for his work entitled The Book ofKnowledge ofIngenious Mechanical Devices. This book is a description of 50 different mechanical devices